Anticorruption in history from antiquity to the modern era - Kroeze, Ronald; Vitória, André; Geltner, Guy 1974- (Oxford University Press, 2018)
The book addresses a wide range of historical contexts: Ancient Greece and Rome, Medieval Eurasia, Italy, France, Great Britain and Portugal as well as studies on anticorruption in the Early Modern and Modern era in Romania, the Ottoman Empire, the Netherlands, Germany, Denmark, Sweden and the former German Democratic Republic.